Burnout, eating behaviour traits and dietary patterns. Issue 2 (20th November 2019) - Chui, Helena; Bryant, Eleanor; Sarabia, Carmen; Maskeen, Shames; Stewart-Knox, Barbara
Abstract : Purpose: The purpose of this research has been to investigate whether burnout and eating behaviour traits were associated with food intake. Design/methodology/approach: Participants ( n =109) 78 per cent female, mean age 39 years, were recruited from various occupations within a UK university to complete an on-line survey. Dietary habits were measured using Food Frequency Questionnaire (FFQ), burnout using the Maslach Burnout Inventory (MBI) and eating behaviour traits using the Three Factor Eating Questionnaire (TFEQ) R18. Findings: Principal component analyses of FFQ responses revealed four dietary patterns: fast/junk food (+chicken and low fruit/vegetables); meat/fish; dairy/grains; beans/nuts. Dietary patterns were examined using multiple regression analysis as outcome variables with age, gender, burnout and eating behaviour traits as explanatory variables. More frequent consumption of "junk/fast food" was associated with lower TFEQ-Cognitive Restraint, higher TFEQ-Uncontrolled Eating (UE), lower MBI-Emotional Exhaustion and higher MBI-Depersonalisation. More frequent consumption of beans/nuts was associated with higher TFEQ-UE and higher MBI-Emotional Exhaustion. Models for meat/fish and grains/dairy dietary patterns were not significant. Research limitations/implications: Burnout may need to be considered to reduce junk food consumption in higher education employees. Causality between burnout, eating behaviour traits and food consumption requires further investigation on larger samples. Originality/value: This appears to be the first study to have explored associations between burnout, eating behaviour traits and dietary patterns.